2014
DOI: 10.1002/star.201400018
|View full text |Cite
|
Sign up to set email alerts
|

Starch physicochemical properties of waxy proso millet (Panicum Miliaceum L.)

Abstract: Starches of four varieties of waxy proso millet were examined in terms of granule morphology, amylose, transparency, retrogradation, pasting, and thermal properties. The starches had great numbers of large polygonal granules with smooth edges, small numbers of small spherical granules, and an average granule size of 6.12 mm. Compared with the starches of non-waxy proso millet and maize, the starches of the waxy proso millet varieties had lower amylose contents (0.21%) and higher phosphorus contents (1.85 mg/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
4
34
1
Order By: Relevance
“…Unlike other plants, proso millet has a short growing period of only about 10–11 weeks, requires little water, and it can be extensively cultivated at a wide range of altitudes such as the Middle East, Europe, Russia, India, and China . Proso millet grains are rich in protein, starch, lipids, dietary fibres, and many trace elements such as calcium, iron, magnesium, and zinc . It has been reported that millet grains are comparable or better than common cereals such as wheat, rice, and oats in the nutritive parameters including protein, mineral and vitamins, and the nutrient components of protein, saccharide, and lipids in millet grains are in proper proportions .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike other plants, proso millet has a short growing period of only about 10–11 weeks, requires little water, and it can be extensively cultivated at a wide range of altitudes such as the Middle East, Europe, Russia, India, and China . Proso millet grains are rich in protein, starch, lipids, dietary fibres, and many trace elements such as calcium, iron, magnesium, and zinc . It has been reported that millet grains are comparable or better than common cereals such as wheat, rice, and oats in the nutritive parameters including protein, mineral and vitamins, and the nutrient components of protein, saccharide, and lipids in millet grains are in proper proportions .…”
Section: Introductionmentioning
confidence: 99%
“…Proso millet grains are rich in protein, starch, lipids, dietary fibres, and many trace elements such as calcium, iron, magnesium, and zinc . It has been reported that millet grains are comparable or better than common cereals such as wheat, rice, and oats in the nutritive parameters including protein, mineral and vitamins, and the nutrient components of protein, saccharide, and lipids in millet grains are in proper proportions . Proso millet is used for human consumption, livestock forage, and as bird seed around the world.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical and structural properties of starch affect the functional properties of heated starch suspensions, including their viscosifying and gelling properties, digestibility, and frozen storage stability. Variety, genetics, growth conditions, and climate affect starch granule properties ; therefore, changes in these factors contribute to different starch functionalities.…”
Section: Introductionmentioning
confidence: 99%